Formulation of multipurpose grease using waste of palm oil manufacturing - Norazman, Daud (2010)

(untitled)
Waste palm oil manufacturing has significant potential as a base fluid and thickener agent for grease formulation. Vegetable oils are promising candidates as base fluid for eco-friendly lubricants because of their excellent lubricity, biodegradability, viscosity-temperature characteristic and low volatility. Spent bleaching earth is suitable for the substitute for thickener agent in grease formulation. This paper presents the effective and ability of grease by using natural material. Performance characteristics of greases used for industrial and automotive application are largely depending on the hardness. Grease hardness was determined using standard test methods. Results indicate that the percent combining spent bleaching earth with fume silica in formulated grease are directly proportional with temperature weight loss but it has indirectly proportional to the penetration value and percent ash content (wt%). Therefore, developed greases can be a good substitute for mineral oil based greases in industrial, agriculture, forestry and marine application.